2013
DOI: 10.1186/1742-9994-10-38
|View full text |Cite
|
Sign up to set email alerts
|

Directional compass preference for landing in water birds

Abstract: IntroductionLanding flight in birds is demanding on visual control of velocity, distance to target, and slope of descent. Birds flying in flocks must also keep a common course of landing in order to avoid collisions. Whereas the wind direction may provide a cue for landing, the nature of the landing direction indicator under windless conditions has been unknown. We recorded and analysed landing directions of 3,338 flocks in 14 species of water birds in eight countries.ResultsWe show that the preferred landing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…A preference for this axis, as observed in our study for silvery mole-rats and Talas tuco-tucos, is common in studies on magnetic orientation (e.g. Malkemper et al, 2015, Oliveriusová et al, 2014, Phillips, 1986 and magnetic alignment (for review see Begall et al, 2013, and is observable in diverse contexts: landing in waterfowl (Hart et al, 2013), escape in roe deer (Obleser et al, 2016), activity in cattle and deer (Begall et al, 2008), flamingos (Nováková et al, 2017), corvids (Pleskač et al, 2017), wild boars and warthogs (Červený et al, 2017), carps (Hart et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…A preference for this axis, as observed in our study for silvery mole-rats and Talas tuco-tucos, is common in studies on magnetic orientation (e.g. Malkemper et al, 2015, Oliveriusová et al, 2014, Phillips, 1986 and magnetic alignment (for review see Begall et al, 2013, and is observable in diverse contexts: landing in waterfowl (Hart et al, 2013), escape in roe deer (Obleser et al, 2016), activity in cattle and deer (Begall et al, 2008), flamingos (Nováková et al, 2017), corvids (Pleskač et al, 2017), wild boars and warthogs (Červený et al, 2017), carps (Hart et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Our results were subsequently confirmed in an independent study by Slabý et al (Slaby, Tomanova, and Vacha 2013). In other studies we found magnetic alignment in hunting foxes , carps schooling in circular tubs (Hart et al 2012), and mallard ducks landing on water (Hart et al 2013). We concluded that magnetic alignment might help animals to synchronize and coordinate movement in a group, organize cognitive (mental) maps, measure the distance and the slope, and maybe enhance (focus) selective sensory attention.…”
supporting
confidence: 85%
“…Following this first finding, a growing number of studies have been published around this topic (Begall et al, 2013, and references therein) with the most recent studies largely focusing on vertebrates (e.g. Hart et al, 2013aHart et al, , 2013bSlaby et al, 2013;Malkemper et al, 2015;Obleser et al, 2016;Čapek et al, 2017;Nováková et al, 2017;. The adaptive significance of magnetic body alignment remains elusive (Begall et al, 2013), and only in a few cases is there some support for plausible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is surprising that birds have only rarely been included in studies of magnetic body alignment. Moreover, when birds have been used in body alignment studies, they have only been observed performing specific activities in their natural habitat, such as landing in ducks and geese (Hart et al, 2013a), foraging in corvids and drinking in domestic chickens (Čapek et al, 2017), and not studied in the lab. In contrast, magnetic orientation has been extensively studied in migratory songbirds in modified so-called Emlen funnels (Emlen and Emlen, 1966), in the past 50 years (e.g.…”
Section: Introductionmentioning
confidence: 99%